Modular AI applications following the Sens4U approach = Modułowa aplikacja sztucznej inteligencji bazująca na rozwiązaniu Sens4U - Wołoszyn, Kamil; Michta, Emil; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
This paper presents the concepts of a universal, modular tool that will enable rapid development of AI applications. The goal of the conceptual tool is versatility in terms of changing the environment, as well as integration of different types of sensors to perform a specific task. The use of the Sens4U approach will facilitate the entire process of building AI applications and simplify the testing process.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne